Surface construction of nitrogen-doped chitosan-derived carbon nanosheets with hierarchically porous structure for enhanced sulfacetamide degradation via peroxymonosulfate activation : maneuverable porosity and active sites - Chen, Xiao (2021)
Nitrogen-doped chitosan-derived carbon nanosheets with hierarchically porous structure were synthesized via a facile pyrolysis treatment of chitosan/urea/NaHCO3 mixture (denoted as CNU). The contents of reactive functionalities, graphitization degree and porous structure of CNU can be effectively tailored by pyrolysis temperature (Tp). The outstanding peroxymonosulfate (PMS)-activation ability of CNU800 (prepared at Tp = 800 °C) for sulfacetamide (SAM) degradation related to its high level of C=O/C (23.7%) and graphitic N/C (4.8%), relatively high graphitization degree, and its large specific surface area and hierarchically porous structure. The introduction of urea in the presence of NaHCO3 during chitosan pyrolysis facilitated the formation of the graphene-like carbocatalyst with hierarchically porous structure and an enhanced PMS-activating activity. The effect of catalyst loading, PMS dosage and common matrix species on PMS activation by CNU800 for SAM degradation was investigated. Quenching experiment and electron paramagnetic resonance collectively revealed that non-radical oxidation (e.g., singlet oxygen (1O2)) was the dominant PMS-activating pathway in the CNU800/PMS/SAM system. The main SAM degradation pathway was also proposed. The conversion between N bonding configurations partially deactivated CNU800. This study deepens the understanding of biomass-based carbocatalyst for environmental remediation.